Mitigating Surface Energy and Core-Shell Interface Strain of Yb3+-Doped ZnSe-Based Quantum Dots for Pure-Blue Emission QLED Devices - Hu, Zhenyu (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.